Episodic Earthquakes Controlled by the Migration of Crustal Fluids and Fault Valve Behavior - Zikun Zhou; Nian Yu; Tianqi Wang; Wenxin Kong; Huang Chen; Tianyang Li (Geophysical Research Letters)
Abstract The Eryuan–Yangbi seismic zones in northwestern Yunnan Province, China, feature intersecting faults and geothermal activity. Persistent yet intermittent earthquakes occur here, though not linked to known faults, suggesting a novel mechanism. A 3–D resistivity model reveals that seismic events align with low‐resistivity zones in the middle‐upper crust. Middle‐crust anomalies indicate crustal melts, while shallow anomalies likely represent saline fluids released from the melts. Fluid accumulation increases pore pressure, weakening faults and triggering slip. Once a critical stress threshold is reached, fault‐valve behavior enhances permeability, facilitating fluid migration and seismic activity. Following earthquakes, permeability decreases as fractures seal, initiating a new cycle of fluid buildup and stress accumulation. Continuous crustal flow from the Tibetan Plateau replenishes the melts, driving ongoing seismicity in the region.